EXTREME WEATHER AND CLIMATIC EVENTS ON AGRICULTURE AS A RISK OF SUSTAINABLE DEVELOPMENT - Vesela, Radović; Pejanović, Radovan; Marinčić, Dušan (Economics of Agriculture, 2015)
The Republic of Serbia suffers severe consequences caused by extreme weather and climatic events. Impact of these events on agriculture is significant, especially having in mind the link of agriculture to the wider scope of implementation sustainable development concept. This paper has as a main goal to promote a strategic approach to protect agriculture from these negative impacts. Using social science methodology, after analyses of numerous data source, authors in the paper shows the existing gap in this field. Hence, results confirmed that, the weakest link in the agriculture protection lies in inadequate level of coordination between stakeholders, and insufficient response capacities of local communities. Recommendation is that Serbia should address needs for create action in a process of mitigation consequences caused with extreme weather and climatic events on through broad based collaboration among all stakeholders. After that action local community will be able to improve its sustainable development performance.